2013
DOI: 10.5740/jaoacint.12-423
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Residues of Cyantraniliprole and Its Metabolite J9Z38 in Watermelon and Soil Using Ultra-Performance Liquid Chromatography/Mass Spectrometry

Abstract: A method was developed for the determination of cyantraniliprole (HGW86) and its metabolite J9Z38 in watermelon and soil by ultra-performance LC (UPLC)/MS/MS. Target compounds were extracted by acetonitrile-water, cleaned up on a silica gel column, and determined by UPLC/MS/MS. Average recoveries of cyantraniliprole and J9Z38 in watermelon and soil at three levels (0.01, 0.1, and 0.5 mg/kg) ranged from 85.71 to 105.74%, with RSDs of 0.90-6.34%. The LOQs for cyantraniliprole and J9Z38 were determined to be 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Therefore, the concentrations of cyantraniliprole in corn plants might be quickly diluted during rapid plant growth in the summer. In addition, the dissipation of chlorantraniliprole in the corn plants ( t 1/2 = 3.02–3.21 days) was similar to that in cauliflower ( t 1/2 = 3.86 days), watermelon ( t 1/2 = 2.7 days), cucumber ( t 1/2 = 2.2 days) and tomato ( t 1/2 = 2.8 days) . The anthranilic diamide insecticide chlorantraniliprole can be distributed throughout the high lipid content matrices in crops due to its greater lipophilic character .…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the concentrations of cyantraniliprole in corn plants might be quickly diluted during rapid plant growth in the summer. In addition, the dissipation of chlorantraniliprole in the corn plants ( t 1/2 = 3.02–3.21 days) was similar to that in cauliflower ( t 1/2 = 3.86 days), watermelon ( t 1/2 = 2.7 days), cucumber ( t 1/2 = 2.2 days) and tomato ( t 1/2 = 2.8 days) . The anthranilic diamide insecticide chlorantraniliprole can be distributed throughout the high lipid content matrices in crops due to its greater lipophilic character .…”
Section: Discussionmentioning
confidence: 61%
“…Watermelon rinds are used for making pickles, and sometimes used as a vegetable in various ethnic recipes including Chinese, Indian, and Thai [5,[31][32][33]. In this study, the possible risk of eating watermelon rinds was investigated by comparing the contents of pesticides in the flesh and the whole watermelon samples.…”
Section: Discussionmentioning
confidence: 99%
“…Watermelon is eaten as fresh fruit and is mainly used to make products such as juices, nectars, and fruit cocktails. Even the by-products, such as peel and seed, can be made into pickles, preserves, and other foods [5]. Thai people commonly use watermelon peel as a vegetable ingredient in their curry dishes (watermelon rind sour curry).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that cyantraniliprole may be metabolized or transformed into IN-J9Z38 during cultivation. Our observation of this metabolite sparks interest because other studies have reported non-detectable or trace levels of IN-J9Z38 residues in Chinese cabbage, rice, tomatoes, cucumbers, and soil 15,19,20,29 .…”
Section: Resultsmentioning
confidence: 84%
“…IN-J9Z38 is a metabolite generated by the ring closure of cyantraniliprole, and this compound is frequently formed as a result of environmental degradation or plant metabolism of cyantraniliprole 13,14 . In many studies, residual patterns of cyantraniliprole have been reported in soil, cucumbers, rice, tobacco, tomatoes, and watermelons 1520 . However, to the best of our knowledge, there have been no studies on the residual behavior of cyantraniliprole in any millet species including proso millet.
Figure 1Chemical structure of cyantraniliprole ( A ) and IN-J9Z38 ( B ).
…”
Section: Introductionmentioning
confidence: 99%